A Constructed Wetland System to Remove Cd from Irrigation Water - DONG Sijun; HE Zhongxiang; PENG Ou; HUANG Xinming; WU De; ZHANG Puxin; TIE Boqing (Guan'gai paishui xuebao, 2021)
【Background】 Soil and water contamination by heavy metals has become an environmental concern worldwide. In China, wastewater produced from mining or mine-tailings leaching has resulted in heavy metals migrating into downstream water bodies and entering food chains following irrigation with such waters. Removing heavy metals from water prior to irrigation is hence vital to prevent them from ending up in the food chain. 【Objective】 The aim of this paper is to present the results of an experimental study on the efficacy of a constructed wetland system to remove Cd from wastewaters emanating from different sources in rice-growing regions in Hunan province. 【Method】 The system comprises a planted pond and an adsorption pond, and we examined its efficacy by treating two types of wastewater: one was from coal mining (DX) and the other one was industrial wastewater (ST), with Cd concentration in both exceeding the national standard. For each wastewater, we measured its Cd removal rate from the system as well as Cd content in rice grains following irrigation with the two treated wastewaters. 【Result】 The average Cd concentration in the inflow water was 6.86 μg/L for ST and 4.56 μg/L for DX, and the average Cd concentration in the outflow water was 0.81 μg/L for the former and 1.33 μg/L for the latter. The system was hence more effective for removing Cd from the industrial wastewater than for the coal mining wastewater with the removal rate being 88.13% for the former and 70.76% for the latter. Irrigating brown rice using the treated ST and DX wastewater reduced Cd content in the grains by 37% and 58% respectably, compared to those irrigated with the wastewaters without any treatment. 【Conclusion】 The pilot system comprising a planted pond and an adsorption pond can move Cd from the wastewaters. In terms of removal rate, the system is more effective for industrial wastewater, while in terms of reducing Cd translation into rice grains, it is more effective for treating the coal mine wastewater.